An alleged homily on the paralytic by John Chrysostom in the codex Athonensis, Lauras A 112 (Eustratiadis 112) - Gârbacea, Radu (HTS teologiese studies, 2022)
Through the efforts of the Institut de Recherche et d’Histoire des Textes (IRHT), a list of manuscripts is available that preserves homilies on the healing of the paralytic. Included in this list is the codex Athonensis, Lauras A 112 (Eustratiadis 112), which, according to those who provided its second description, preserves in the last four folios ‘a homily on the paralytic by John Chrysostom’. After a brief presentation of what is known about this codex, this article offers a detailed examination of the codex’s last four folios, revealing that the description of them by Spyridon Lauriotis and Sophronios Eustratiadis is inaccurate.Contribution: This article provides the first thorough examination of the last four folios of the codex Athonensis, Lauras A 112 (Eustratiadis 112), demonstrating that they do not contain ‘a homily on the paralytic by John Chrysostom’ but rather several fragments of homilies on Thomas, Mid-Pentecost and the Ascension. Thus, the article contributes to the description of the codex and to the identification of a previously unknown manuscript witness to several homilies.